The relationship between the environment and technical experimentation in the works of artists Hanaa Malallah and Ghassan Ghaib (Al-Academy, 2025)
The current research, titled "The Relationship between the Environment and Technical Experimentation in the Works of Artists Hanaa Malallah and Ghassan Ghaib," addresses the problem of the environment and technical experimentation being closely linked, as technical experimentation requires a specific environment to effectively develop and implement tests and experiments. It is worth noting that the environment is not only the place where technical experimentation takes place, but it may also be a primary factor that influences the outcome of the experiments or determines their effectiveness. Through this research, the researcher examined the techniques used, the employment of materials, and their diversity in the artistic production employed by the artists (Hana Malallah and Ghassan Ghaib). The researcher worked to reshape these techniques with different technical and color treatments at the performance and technical levels in a unique and noticeable manner. The research objective is to identify the relationship between the environment and technical experimentation in the works of artists Hanaa Malallah and Ghassan Ghaib. The research includes four chapters. The first chapter addresses the concept of technical experimentation. The second chapter addresses the environment and its relationship to technical experimentation in the formation of artworks. The third chapter addresses technical experimentation in the works of Hanaa Malallah. Chapter Four: Technical Experimentation in the Works of Ghassan Ghaib. Based on these four chapters and to achieve the research objective, a number of results and conclusions were reached, including:Artists Hanaa Malallah and Ghassan Ghaib continue to emphasize the use of the same technique repeatedly and exclusively in displaying most of their works. This is achieved by relying on the material used to demonstrate the technique, or by relying on the display of texture as a fundamental element in display techniques.The experimental artist develops cognitive (mental) plans that precede the production and completion of his artworks. He addresses all technical variables on the surface of his pictorial works, while leaving room for new developments that emerge during the completion process